The important issues to consider regarding powers of attorney - Tuiro Layme, Axel Enrique (2024)
Every day several legal acts are celebrated in Peruvian society, so knowing the legal figure of power is of utmost importance for all persons who celebrate legal acts on behalf of others, since errors can be made by not knowing about this legal mechanism. In this work, this guides precisely to make known the relevant issues that must be considered before executing a power of attorney, which the people must take into account, since ignorance can have serious consequences not only for the persons that execute the power of attorney, legal act, but also third persons.